Espíritu emprendedor y la creación de micro y pequeñas empresas por estudiantes de educación superior - Mitma Pérez, Rufino Agustín (2020)
Objective: To determine the relationship of the entrepreneurial spirit and the creation of micro and small businesses in students of the Public Pedagogical Higher Education Institute - Huancavelica. Method: The research is basic, correlational, the sample was 114 students, the questionnaire was applied to evaluate the variable, the entrepreneurial spirit and another to evaluate the level of creation of micro and small businesses, the data was processed with Excel and SPSS and analyzed with Pearson's r correlation and the t-student test. Results: In the first variable, 14.9% show a low level, 46.5% a regular level and 38.6% show a high level of entrepreneurial spirit. Likewise, in the second variable, on the creation of micro and small businesses, 12.3% show a low level, 56.1% a regular level and 31.6% a high level, of micro and small business creation. Business. Pearson's r coefficient of 0.915 states that entrepreneurship is significantly related to the creation of micro and small businesses. Conclusion: Obtaining the Pearson r coefficient of 0.915, affirms, the entrepreneurial spirit is significantly related to the creation of micro and small companies in IESPPH students, the general hypothesis being validated by having obtained a Tc = 24.00> Tt = 1.66.